2012
DOI: 10.5713/ajas.2011.11473
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of WSSV ORF 199 and Shrimp Ubiquitin Conjugating Enzyme in WSSV Infected Penaeus monodon

Abstract: White spot syndrome virus (WSSV) is one of the major viral pathogens affecting shrimp aquaculture. Four proteins, WSSV199, WSSV 222, WSSV 249 and WSSV 403, from WSSV are predicted to encode a RING-H2 domain, which in presence of ubiquitin conjugating enzyme (E2) in shrimp can function as viral E3 ligase and modulate the host ubiquitin proteasome pathway. Modulation of host ubiquitin proteasome pathway by viral proteins is implicated in viral pathogenesis. In the present study, a time course expression profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This is supported by [26] who reported that the RING-H2 protein WSSV249 from WSSV may function as an E3 ligase by sequestering PvUbc for viral pathogenesis in shrimp [26]. The upregulation of PmUbc at 24 hpi in WSSV challenged shrimp was revealed using semi-quantitative and real time PCR [16]. Many findings have shown that viral infection can up-regulate expression of ubiquitin [19,18], suggesting that the ubiquitin system may play a key role in the course of viral infection.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is supported by [26] who reported that the RING-H2 protein WSSV249 from WSSV may function as an E3 ligase by sequestering PvUbc for viral pathogenesis in shrimp [26]. The upregulation of PmUbc at 24 hpi in WSSV challenged shrimp was revealed using semi-quantitative and real time PCR [16]. Many findings have shown that viral infection can up-regulate expression of ubiquitin [19,18], suggesting that the ubiquitin system may play a key role in the course of viral infection.…”
Section: Discussionmentioning
confidence: 78%
“…In our previous work the expression profiles of PmUbc was compared with the expression of WSSV 199 and WSSV 249. The expression patterns of PmUbc, in comparison with WSSV 199 and 249 speculated that the ubiquitin conjugating enzyme (PmUbc) is modulated by the WSSV proteins [16]. Four proteins of WSSV namely WSSV 199, WSSV 222, WSSV 249 and WSSV 403 are known to contain RING H2 domains [29,26] which in presence of ubiquitin conjugating enzyme (E2) in shrimp can function as E3 ligase can modulate the ubiquitin proteosome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of the ubiquitin protein was estimated to be 1.85 and 1.67 lg/mg of the total protein in gills and muscle, respectively at 18 hpi. We have also earlier reported the expression profiles of WSSV RING finger domain gene, WSSV ORF 199 and shrimp ubiquitin conjugating enzyme (PmUbc) genes [5]. A significant increase in PmUbc expression at 24 hpi was observed followed by a decline till 72 hpi.…”
mentioning
confidence: 66%
“…WSSV, the largest animal virus known to affect cultured shrimp is a sole member of the monotypic family Nimaviridae, genus Whispovirus [2]. It has a circular dsDNA genome of about 300 kbp that contains approximately 185 open reading frames (ORFs) [5]. Due to its serious impact on shrimp aquaculture, there is an urgent need to understand WSSV and to unveil the underlying mechanisms involved in WSSV pathogenesis in shrimp.…”
mentioning
confidence: 99%
“…with conjugating enzyme (E2) in shrimp) and act as viral E3 ubiquitin protein ligases to inhibit apoptosis and affect viral pathogenesis [46, 47]. Injection of recombinant Fenneropenaeus chinensis ubiquitin-conjugating enzyme E2 has been shown to reduce the mortality of shrimp challenged with WSSV, inhibit replication of WSSV and bind to (and ubiquitinate) WSSV RING domain-containing proteins [53], and ubiquitin C expression is up-regulated when F. chinensis are challenged by WSSV [54].…”
Section: Discussionmentioning
confidence: 99%